Effects of heat stress on concentrations of thyroid hormones of workers in a foundry industry - mohammad javad jafari; sahar norloei; Leila Omidi; soheila khodakarim; Davood Bashash; mohammad bagher abdollahi (طب کار)
Introduction: Heat-related diseases are common disorders in many industries. Heat stress can cause changes in the secretion of some plasma hormones. The aim of this study was to determine the effects of heat stress on concentrations of serum triiodothyronine (T3) and thyroxine (T4) hormones among foundry workers.